Análise da retenção de caixa e alavancagem financeira como recursos complementares ou substitutos nas empresas brasileiras de capital aberto - Ferreira , Marília Paranaíba (2018)
This research investigated whether Brazilian publicly traded companies classified as financially restricted and unrestricted used cash holdings and financial leverage in a complementary or substitutive way, and if the financially restricted companies kept more cash than the unrestricted ones in the period between January 2010 and December 2016. The data were collected quarterly on the basis of Economatica® and the principal components factorial analysis technique was adopted to classify the companies in restricted and unrestricted. The sample with 108 companies, 55 restricted and 53 unrestricted, was analyzed through multiple regressions with unbalanced panel data and the results indicated that 1) in financially restricted companies, cash holdings and financial leverage are complementary sources of financing; 2) cash holdings and financial leverage are sources of substitute financing in financially unrestricted companies; and 3) financially restricted Brazilian companies retained, on average, more cash than unrestricted ones. The theoretical contribution of this study was the construction of a different perspective of the Trade-Off and Pecking Order theories, in the sense that the first treats the resources as complementary and the second as substitutes, and the empirical was the choice of the method used to segregate the companies in financially restricted and unrestricted.